Redescription and distributional range extension of the Speckled Siphonfish, Siphamia guttulata (Pisces: Apogonidae) - Pogonoski, John J.; Gon, Ofer; Appleyard, Sharon A. (Zootaxa, 2020)
During seabed biodiversity surveys between 2003 and 2005 from the Torres Strait (Papua New Guinea) to the southern Great Barrier Reef (Queensland), hundreds of Siphamia specimens were collected. After Gon & Allen’s (2012) revision allowed greater interrogation of the Siphamia species present, a re-examination of preserved and frozen Siphamia specimens at the CSIRO Australian National Fish Collection (ANFC) was warranted. The material was re-identified as four commonly collected species (S. cuneiceps, S. roseigaster, S. tubifer, and S. tubulata) and a fifth unidentified species that appeared to key to S. guttulata, previously known only from the type locality. Further detailed investigations including an analysis of meristic, morphometric and COI barcoding data confirmed the identity of S. guttulata from almost the entire length of the Great Barrier Reef, Queensland, from the Torres Strait in the north to the Northumberland Islands Group in the south. This study provides a redescription of Siphamia guttulata and highlights the importance of re-assessing the taxonomic status of museum material after revisionary studies.